Assessment of risk factors for enteric fistula and intra-abdominal sepsis in patients with open abdomen in trauma: An original research - Sukumaran Vengail; Dharamveer Chandrakar; Ajit K Naik; Amiya K Nayak; Akriti Mahajan; Priyanjali Dutta (Wolters Kluwer Medknow Publications, 2023)
Introduction: In emergency surgeries, open abdomen or laparostomy, especially with perforated viscus, has been used primarily to prevent delayed ventral hernia, burst abdomen, and abdominal compartment syndrome. In the present study, the clinical and resuscitative factors that are linked with open abdomen morbidity are evaluated. Material and Methods: A retrospective analysis was done for all the subjects who were admitted at the tertiary care center between May 2020 and May 2022 for the open abdomen surgeries. These patients were examined to see whether they needed more postoperative care than usual, including the need for resuscitative treatments and other critical clinical indicators. Patients were evaluated if they had any complications. The data that were collected were analysed for any variance using analysis of variance considering P <.05 as significant. Results: A total of 100 subjects were analysed in this study. Forty nine patients had intra-abdominal sepsis of the 100 cases examined from historical case records and 1 had entero-cutaneous fistulas. These patients did not necessitate additional actions for intensive care unit care, resuscitation, an chest infection, extended hospital stay, or any disabilities compared to those who did not undergo laparotomy during the same period. In this group of patients with open abdomens, the immediate postoperative period was not linked to an increase in resuscitation efforts or a load on clinical staff. Once patients are stabilized, early definitive abdominal closure is advised to prevent problems associated to laparostomies. Conclusion: The quantity of initial fluid revival and the coagulation factors at the time of admission are not related to intra-abdominal sepsis and enteric fistula following laparostomy after significant abdominal injuries.